KEBERADAAN BAKTERI PATOGEN Vibrio cholerae PADA BEBERAPA HASIL PERIKANAN YANG DIJUAL DI PASAR TRADISIONAL KOTA DENPASAR - Widyastana, I Wayan Yogi; Kawuri, Retno; Dalem, Anak Agung Gde Raka (Metamorfosa: Journal of Biological Sciences, 2015)
The purpose of this research was to find out the existence of Vibrio cholerae, bacteria that may cause cholera disease , in some fishery products in Denpasar traditional market, Bali. This research used samples taken from three different fisheries products: tuna fishes ( Euthynnus affinis ), shrimps ( Penaeus indicus ), and shellfish ( Anodonta sp.). They were taken from three traditional markets in Denpasar City: Ketapian, Kumbasari, and Pidada Markets. All samples were cultured on Alkaline Peptone Water (APW) media, continued by Thiosulfate Citrate Bile Salt Sucrose (TCBS), and then Biochemical Test and Serology Test undertaken. The results of this study showed that two (7.4%) samples taken from Ketapian Market were proved to be positive containing pathogenic bacteria of V. cholerae ; they were the shrimps with UA2 code and the shellfish with KA2 code. Meanwhile, there were no V. cholerae contaminations proven to exist in two other kind of products in other two traditional markets.
Keywords: Vibrio cholerae, Denpasar City traditional market, fishery products, Bali